2016
DOI: 10.1159/000445573
|View full text |Cite
|
Sign up to set email alerts
|

Osthole Induces Cell Cycle Arrest and Inhibits Migration and Invasion via PTEN/Akt Pathways in Osteosarcoma

Abstract: Background/Aims: Osteosarcoma is the second highest cause of cancer-related death in children and adolescents. Majority of osteosarcoma patients (90%) show metastasis. Previous reports revealed that osthole showed antitumor activities via induction of apoptosis and inhibition of proliferation. However, the potential effects and detailed molecular mechanisms involved remained unclear. Methods: Cell viability was analyzed by MTT assay in osteosarcoma cell lines MG-63 and SAOS-2. Cell cycle was detected by flow c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
32
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(34 citation statements)
references
References 33 publications
(36 reference statements)
1
32
0
1
Order By: Relevance
“…Several epidemiological and preclinical studies have highlighted the potential benefits of using flavonoids for cancer prevention. Osthole has been shown to exert anti-cancer effects via the PTEN/Akt signaling pathway [44], and quercetin is one flavonoid whose effects have been widely reported [45-47]. Quercetin exerts its anticancer effects by inducing cell cycle arrest, apoptosis, and differentiation and by suppressing MMP secretion [48].…”
Section: Discussionmentioning
confidence: 99%
“…Several epidemiological and preclinical studies have highlighted the potential benefits of using flavonoids for cancer prevention. Osthole has been shown to exert anti-cancer effects via the PTEN/Akt signaling pathway [44], and quercetin is one flavonoid whose effects have been widely reported [45-47]. Quercetin exerts its anticancer effects by inducing cell cycle arrest, apoptosis, and differentiation and by suppressing MMP secretion [48].…”
Section: Discussionmentioning
confidence: 99%
“…Cyclin–CDK complexes are precisely and strictly regulated to prevent abnormal proliferation. There are two families of inhibitors that block the catalytic activity of cyclin-CDK complexes, namely inhibitor of CDK4 (INK4) family which only bind to CDK4/6, and KIP/CIP family including p21 WAF1/CIP1 and p27 KIP1 , which can inhibit all cyclin-CDK complexes [11, 27, 33, 34]. A gene knockout study in mice confirmed that p21 and p27 are important partners in mammalian cardiomyocyte [35].…”
Section: Discussionmentioning
confidence: 99%
“…U-2OS and SaOS-2 cells were cultured in McCoy’s 5A (Sigma, M4892) with 10% fetal bovine serum (CLARK, FB25015), MG-63 cells were cultured in MEM (Gibco 41500-034) with 10% fetal bovine serum, penicillin (100 U/mL) and streptomycin (100 U/mL) in a humidified incubator (Thermo Fisher, Runcorn, Cheshire, UK) with 5% CO 2 at 37°C [22, 23]. …”
Section: Methodsmentioning
confidence: 99%
“…The reaction was terminated by removing the supernatant, adding dimethyl sulfoxide (150µl/well), and shaking for 10 min at room temperature. The absorbance was measured at 490 nm in a spectrophotometer [22]. …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation